2003
DOI: 10.1103/revmodphys.75.949
|View full text |Cite
|
Sign up to set email alerts
|

Advances in atomic force microscopy

Abstract: This article reviews the progress of atomic force microscopy in ultrahigh vacuum, starting with its invention and covering most of the recent developments. Today, dynamic force microscopy allows us to image surfaces of conductors and insulators in vacuum with atomic resolution. The most widely used technique for atomic-resolution force microscopy in vacuum is frequency-modulation atomic force microscopy (FM-AFM). This technique, as well as other dynamic methods, is explained in detail in this article. In the l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
1,480
1
42

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,948 publications
(1,533 citation statements)
references
References 180 publications
(325 reference statements)
10
1,480
1
42
Order By: Relevance
“…The TNT films were characterized by atomic force microscopy (AFM) [49][50][51], which revealed that the nanotubes well covered the whole surface of the silicon wafer, the OWLS chip and the glass plate homogeneously (Fig. 1) The arithmetic average roughness (R a ) and root mean squared roughness (RMS) [13,52] of the surface were calculated from the AFM data, and were approximately 3.9 nm and 5.3 nm, respectively.…”
Section: Surface Morphology and Optical Characterization Of The Titanmentioning
confidence: 99%
“…The TNT films were characterized by atomic force microscopy (AFM) [49][50][51], which revealed that the nanotubes well covered the whole surface of the silicon wafer, the OWLS chip and the glass plate homogeneously (Fig. 1) The arithmetic average roughness (R a ) and root mean squared roughness (RMS) [13,52] of the surface were calculated from the AFM data, and were approximately 3.9 nm and 5.3 nm, respectively.…”
Section: Surface Morphology and Optical Characterization Of The Titanmentioning
confidence: 99%
“…Atomic force microscopy's 7 (AFM) ability of visualizing the topography and the property of surfaces and interfaces at a molecular level 8 has enabled a rapid development in the understanding of surface phenomena. Its versatility allows the exploration of hard and soft materials in vacuum 9-12 , in air 13 , but also in complex liquids 14,15 , often allowing imaging at sub-nanometre and sometimes atomic resolution 16 . In dynamic mode 17 (vibrating cantilever), AFM has proven sensitive to the interfacial compliance of viscous liquids and provided quantitative information about the structure of liquid layers between the AFM tip and the solid surface 18 , with, in some cases, atomic resolution 15 .…”
mentioning
confidence: 99%
“…In all cases we obtained atomic-or molecularlevel resolution images with structures corresponding to the expected crystallographic arrangements. Traditionally, AFM resolution does not match that of Scanning Tunnelling Microscopy (STM) because the STM feedback signal decays exponentially with tip-sample distance 16 while it typically decays with a power law on larger distances for AFM 13 . Hence in STM only the very apex of the tip is effectively involved in the imaging 16 , while in AFM a larger portion of the tip contributes to the imaging, making tip sharpness a critical factor.…”
mentioning
confidence: 99%
“…9 This instability can be avoided by oscillating the cantilever. 2 Attractive tip−surface forces slightly reduce the cantilever resonant frequency; the closer the tip approaches, the stronger the attractive force and thus the larger the frequency drop.…”
Section: Operating Principlementioning
confidence: 99%